The testimonial condition of a writer in transition: Memorias curiosas of Juan Manuel Beruti (Anclajes, 2015)
This article examines the testimonial condition of Juan Manuel Beruti (1777-1856). To do so, it provides a brief theoretical review about autobiographical writing and its characteristics in late 18th century and early 19th century, and then performs a discourse analysis of Memorias curiosas, an extensive chronicle about the main events ocurring in the city of Buenos Aires from 1717 to 1855. The definition of “witness,” proposed by Paul Ricoeur, is used to understand the text as a testimony.
Keywords: Argentinine literature; 19th century; Juan Manuel Beruti; literary analysis; memory